PENGGUNAAN DSS AHP, SAW DAN SMART UNTUK MENENTUKAN PRIORITAS PEMBANGUNAN DI KOTA MALANG - Deddy kusbianto; Purwoko Aji (STMIK YADIKA BANGIL, 2016)
Abstract: Economic growth has an important role in poverty reduction and job creation. During the five-year period of last economic growth on Malang City has increased, but when compared with Another City in East JavaMalang City economic growth not as a top grade. Edison added that he had been driving around Malang City. He considered if the potential in this City is big enough to use the community investing. Unfortunately, up to now,people are still not aware of the area with their potentials. In Malang, in conjunction with the issuance of Presidential Instruction No. 3 Year 2003 on National policies and strategies for the development of e-Government, has started the implementation of e-Government development through network building program